2019
DOI: 10.22161/ijeab/4.2.26
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Extension Agents’ Perception of Mobile Phone Usage for Communication with Farmers in EDO South of EDO State, Nigeria

Abstract: The use of mobile phones as means o f communication between the extension agents and local farmers in Edo South was examined to determine the perception of the extension agents on its effectiveness. Fi ftyone (51) respondents were obtained through random sampling using questionnaires to obtain relevant information in the two local government areas; Ovia North East and Ovia South West selected for the study. The result obtained indicated that male extension agents were in majority (72.5%), 54.9% of the sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thus, mobile apps have been highly underutilized for extension of livestock, fishery, and agro-forestry components of EBADP extension services, resulting in low utilization of mobile apps for extension service delivery in EBADP. This finding is not surprising considering the fact that phone calls and short message service (SMS) are the most use features of mobile phones for agricultural extension services in Nigeria (Alakpa, Afolabi and Ighalo, 2019). Constraints to Use of Mobile apps for extension service delivery in EBADP C The results indicate that the low utilization of mobile apps for extension service delivery in EBADP was due to: unavailability of network coverage in rural areas (84%), lack of institutional policy for application of mobile apps in extension service delivery (75%), low ownership of smart phones among farmers due to high cost (73%), poor farmers' knowledge on the use of mobile apps (67%), poor internet connectivity (66%), unstable electricity (64%), and lack/inadequate training programmes on mobile apps use for extension service delivery (48%) ( Table 4).…”
Section: Components Of Extension Services Delivered On Mobile Phone Appsmentioning
confidence: 99%
“…Thus, mobile apps have been highly underutilized for extension of livestock, fishery, and agro-forestry components of EBADP extension services, resulting in low utilization of mobile apps for extension service delivery in EBADP. This finding is not surprising considering the fact that phone calls and short message service (SMS) are the most use features of mobile phones for agricultural extension services in Nigeria (Alakpa, Afolabi and Ighalo, 2019). Constraints to Use of Mobile apps for extension service delivery in EBADP C The results indicate that the low utilization of mobile apps for extension service delivery in EBADP was due to: unavailability of network coverage in rural areas (84%), lack of institutional policy for application of mobile apps in extension service delivery (75%), low ownership of smart phones among farmers due to high cost (73%), poor farmers' knowledge on the use of mobile apps (67%), poor internet connectivity (66%), unstable electricity (64%), and lack/inadequate training programmes on mobile apps use for extension service delivery (48%) ( Table 4).…”
Section: Components Of Extension Services Delivered On Mobile Phone Appsmentioning
confidence: 99%
“…The result suggests that pineapple production in the study area is faced with several problems which might affect its production. Alakpa and Onemolease (2014) had noted that insufficient capital and inadequate farming equipment were the some of the major problems hindering farmers' adoption of improved farm practices that would have improved their production.…”
Section: Factors Associated With the Adoption Of Improved Pineapple P...mentioning
confidence: 99%
“…Faming experience has been reported to influence farmers' decision to adopt innovation. Alakpa and Onemolease (2014) reported that farmers with more farming experience tend to appreciate and consequently adopt improved technology. A possible explanation for the significant relationship between household size and the adoption of improved farm practices in pineapple production could be that farmers with large farm size are likely to cultivate larger expanse of land, produce more and consequently require more production knowledge.…”
Section: Relationships Between Socio-economic Characteristics and Ado...mentioning
confidence: 99%